Prestable ideals and Sagbi bases - Ohsugi, Hidefumi; Hibi, Takayuki (Mathematica Scandinavica, 2005)
In order to find a reasonable class of squarefree monomial ideals $I$ for which the toric ideal of the Rees algebra of $I$ has a quadratic Gröbner basis, the concept of prestable ideals will be introduced. Prestable ideals arising from finite pure posets together with their application to Sagbi bases will be discussed.